Comparison of rna extraction methods for transcript analysis from the psychrophilic yeast, Glaciozyma antarctica - Izwan, B.; Najad-Zamirah, Z.; Farah-Diba, A.B.; Nor-Muhammad, M.; Mohd-Nazalan, M.N; Rosli, M.I.; Abdul-Munir, A.M. (Penerbit Universiti Kebangsaan Malaysia, 2014)
To survive in extremely cold environments, psychrophilic microorganisms produce exopolysaccharides (EPS), which are carbohydrate polymers that constitute a substantial component of the extracellular polymers surrounding cells of these microorganisms. EPS can interfere with RNA extraction and decrease the purity of the RNA extracted from EPS producing microorganisms. In this work, six commercial RNA extraction kits and two published protocols for RNA extraction were evaluated for total RNA extraction from the psychrophilic yeast, Glaciozyma antarctica. All the protocols were optimised to obtain the highest quality of total RNA. The results show that all of the tested commercial kits and the tested conventional methods yielded RNA from G. antarctica, albeit with varying quality. The protocol that utilises TRIzol® reagent was the most effective method for isolating total RNA from G. antarctica of which this protocol resulted in the highest RNA yield and purity compared to other methods. This method of RNA extraction produced RNA of sufficient quality for reverse transcriptase PCR (RT-PCR) to detect the expression of the G. antarctica delta 9-fatty acid desaturase gene as well as for the construction of a G. antarctica cDNA library.